Correlation and Path Coefficient Analysis of Yield and Yield Components of Quality Protein Maize (Zea mays L.) Hybrids at Jimma, Western Ethiopia - Jemal Aman; Kassahun Bantte; Sentayehu Alamerew; Desta Berhe Sbhatu (International Journal of Agronomy)
Maize is one of the most important staple food crops in many parts of Ethiopia. However, it is not used extensively due to its poor nutritional quality and low productivity. It lacks two essential amino acids, namely, lysine and tryptophan. Knowledge of the interrelationships of grain yield and its various causal (contributory) components is very helpful to improve the efficiency of breeding programs using appropriate selection indices. This article reports the findings of a study conducted to determine the nature of relationships of grain yield and its contributing components and to identify those components with significant effects on yield with the intention of using them as selection criteria using path coefficient analysis (PCA). Therefore, PCA has shown that yield per hectare had a significant and positive phenotypic correlation with plant height, ear height, number of kernels per row, and 100-grain weight. Moreover, PCA had a significant and positive genotypic correlation with days to 50% tasseling, plant height, ear height, and 100-grain weight. The highest direct positive effect on yield per hectare was exhibited by ear height. The findings of this study showed that most genotypes are early maturing and are suitable for areas with short rainy seasons and prone to drought.